The Economics of Religion - McCleary, Rachel M. (Journal of Economic Literature, 2023)
Rachel M. McCleary of Harvard University reviews “The Economics of Religion” edited by Robert M. Sauer. The Econlit abstract of this book begins: “Twelve papers examine the interconnection between religiosity and economic principles, highlighting future directions for research in the emerging field of the economics of religion.”